La loi du 3 janvier 1979 (France) et la communication des documents - Charpy, Jacques (La Gazette des archives, 1979)

La loi du 17 juillet 1978 (France) : de la liberté d'accès aux documents administratifs - Gorgeon-Demartres, A. (La Gazette des archives, 1979)

La conservation et la consultabilité des archives contemporaines au Grand-duché de Luxembourg - Spang, Paul (Archives et bibliothèques de Belgique (ABB), 1979)

Les généalogistes et les Archives - Wolff, Christian (Gazette des archives, 1979)
Genealogists and archives. Difficultes encountered and examples of solutions adopted by several archive institutions to meet the increasing number of genealogists. The growing importance of this category of researchers and the risks which they inflict on the preservation of documents make it advisable that archivists adopt a common attitude in their relations with genealogists. Better organisation and discipline of genealogists themselves would make these relations easier.

Le nouvel état des fonds du Bundesarchiv de Coblence : réflexions sur l'accès du public aux archives - Ducrot, Ariane (Gazette des archives, 1978)
After the recent publication of the new Guide to the contents of the Bundesarchiv in Koblenz, some reflexions about the policy of Archives for the publicity of their contents : regulations as to access, finding aids, help given to researchers, etc.